1965
DOI: 10.1002/macp.1965.020890119
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of anionic polymerization of styrene and α‐methylstyrene. Effects of counter‐ion and solvent

Abstract: I n non-terminat ed anionic polymerization the propagating species may be a free anion or an ion-pair and the latter may dimerize to a relatively unreactive species1*2). VCi e wish t o report here some results of an attempt to study systematically the effects of the alkali metal cation and of the solvent on the ARRHENIW parameters in the propagation of ion-pairs involving (a) polystyryl anions and (b) poly-a-methylstyryl anions.X'hese resalts are given here in summary forni i n view of the current interest in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

1967
1967
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…There are, however, lower values of A reported in dioxane, 69 THP, 78 and THF. 46 In some cases with sodium and potassium as the counterions, this is artificial and caused by the small temperature range studied, 78 only down to 2°.…”
mentioning
confidence: 47%
See 1 more Smart Citation
“…There are, however, lower values of A reported in dioxane, 69 THP, 78 and THF. 46 In some cases with sodium and potassium as the counterions, this is artificial and caused by the small temperature range studied, 78 only down to 2°.…”
mentioning
confidence: 47%
“…Because no problems of this type exist for ␣-methylstyrene, Potter and Metz 68 concluded that the process with styrene cannot be as simple as the free-cation chain mechanism suggests and must include other species propagating, including free anions. Because ␣-methylstyrene does not polymerize free radically (except at very high pressures) and only very slowly anionically, 69 this seems a reasonable explanation of the difference between the two monomers. The more recent higher values for the free polystyryl anion in ether solvents average 48 39,42 is, of course, much lower than that reported for bulk monomer.…”
mentioning
confidence: 94%
“…The anionic polymerization system of α‐methylstyrenes usually shows equilibrium behaviors known as the thermodynamically reversible polymerization due to the steric strain caused by the α‐methyl group . The polymerization of AdαMS was first carried out with K‐Naph in THF at −78 °C for 8 h in order to achieve the complete consumption of monomer similar to the previous experiment (run 5).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we newly designed and anionically polymerized an adamantyl‐substituted α‐methylstyrene derivative, 4‐(1‐adamantyl)‐α‐methylstyrene ( AdαMS ), in order to check the polymerizability of the monomer and the thermal properties of the resulting polymer. It is well known that α‐methylstyrene derivatives usually undergo the equilibrium polymerization under the anionic conditions due to the low ceiling temperatures . The polymerization and depolymerization of α‐methylstyrene derivatives reversibly occur under the equilibrium conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The anionic polymerization of styrene has been studied in a series of ethereal solvents of varying dielectric constant, dimethoxyethane (l,2), tetrahydrofuran (3)(4)(5), tetrahydropyran (7)(8)(9), and dioxane (9,10). Evidence has been presented for the presence of three types of active species, the free anion, a solvent-separated ion-pair, and a contact ion-pair, in order of decreasing reactivity.…”
Section: Introductionmentioning
confidence: 99%